A comprehensive stability indicating method for clonidine hydrochloride impurities profiling and degradation analysis in tablet formulations: green metric study - Vijay Arjun Bagul; Sushama Raju Ambadekar; Anand Radheshyam Tiwari (Discover Chemistry)
Abstract This study focuses on the development of a stability-indicating RP-HPLC method for the identification and quantification of impurities associated with Clonidine HCl. The chromatographic separation was achieved using isocratic elution on a Kromasil C8 column (250 × 4.6 mm, 5 µm), with a mobile phase comprising phosphate buffer (pH 6.9) and acetonitrile in a 50:50 (v/v) ratio. The flow rate was maintained at 0.8 mL/min, and a 50µL sample was injected. Detection was performed at 210 nm, with the column temperature set at 30 °C. The method was validated as per ICH Q2 (R2) guidelines and demonstrated specificity, precision, robustness, and linearity over a concentration range from the LOQ to 150% of the specification level. The correlation coefficient (r) was ≥ 0.99, and recovery results across the accuracy range met the established acceptance criteria. To evaluate environmental sustainability, the method was assessed using established green chemistry tools: the Analytical GREEnness (AGREE) metric and the Multi-Objective Green Analytical Procedure Index (MoGAPI). Both assessments confirmed the method’s eco-friendly profile. Forced degradation studies were conducted under acidic, basic, oxidative, photolytic, and thermal conditions. Notable degradation was observed under basic and oxidative stress, confirming the method’s capability to distinguish degradation products. In conclusion, the developed method is robust, accurate, environmentally sustainable, and well-suited for routine impurity profiling of Clonidine HCl in pharmaceutical formulations, thereby ensuring quality assurance and patient safety. Graphical Abstract